2003
DOI: 10.1093/jac/dkg151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the antimitotic natural product dolastatin 10, and related peptides, on the human malarial parasite Plasmodium falciparum

Abstract: Microtubule inhibitors from several chemical classes can block the growth and development of malarial parasites, reflecting the importance of microtubules in various essential parasite functions. With the spread of antimalarial drug resistance, there is an urgent need for new approaches to the chemotherapy of this devastating disease. We investigated the effects of two naturally occurring marine peptides, dolastatin 10 and dolastatin 15, and 10 synthetic dolastatin 10-based compounds (auristatins), on cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…To compare these results with those seen for known microtubule destabilizing and stabilizing drugs, we treated cultures with paclitaxel and vinblastine (Figure 6 B, C). Paclitaxel treatment (1 µM for 6 hours) has been shown to result in the appearance of thick rod-like microtubules whereas vinblastine treatment (20 µM for 6 hours) has the converse effect and results in diffuse tubulin staining [35], [44] in P. falciparum . We treated cultures for 24 hours with lower concentrations of paclitaxel and vinblastine (500 nM and 100 nM respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To compare these results with those seen for known microtubule destabilizing and stabilizing drugs, we treated cultures with paclitaxel and vinblastine (Figure 6 B, C). Paclitaxel treatment (1 µM for 6 hours) has been shown to result in the appearance of thick rod-like microtubules whereas vinblastine treatment (20 µM for 6 hours) has the converse effect and results in diffuse tubulin staining [35], [44] in P. falciparum . We treated cultures for 24 hours with lower concentrations of paclitaxel and vinblastine (500 nM and 100 nM respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The primary antibody used for tubulin immunofluorescence (a kind gift from Dr. Angus Bell, Trinity College, Dublin) was raised in rabbit against a P. falciparum specific beta tubulin peptide [35]. Acyl Carrier Protein (ACP) antibody specific for P. falciparum (a kind gift from Prof. Geoff McFadden, The University of Melbourne) was used for apicoplast immunofluorescence.…”
Section: Methodsmentioning
confidence: 99%
“…The known microtubule inhibitors dolastatin 10 ( Fig. (2)) and auristatin PE were most potent on schizonts, caused growth arrest or delay at the schizont stage, and eliminated normal mitotic structures [92]. Microtubules are considered to have potential as antimalarial drug targets and are already exploited by a number of antiparasitic drugs [93].…”
Section: Thiopeptidesmentioning
confidence: 99%
“…Microtubules are considered to have potential as antimalarial drug targets and are already exploited by a number of antiparasitic drugs [93]. SAR for the dolastatin/auristatin series showed some differences for parasites and human cells but no derivative was clearly parasite-selective [92].…”
Section: Thiopeptidesmentioning
confidence: 99%
“…The antimalarial activity of dolastatin 10, a peptide microtubule inhibitor isolated from the sea hare D. auricularia which is a potent anticancer drug. Although study was described and dolastatin 10 showed potent inhibition of P. falciparum (IC 50 = 0.1 nM) by affecting the schizont stage of intraerythrocytic development, which has the highest concentration of tubulin, the investigators concluded that dolastatin 10 was an "unpromising basis for further antimalarial evaluation" because of the lack of marked selectivity for parasite over mammalian cells (Fennell et al, 2003). The manzamine alkaloids as potential antimalarial agents, Manzamine A was observed to be particularly active against P. falciparum (D6 clone, IC 50 = 4.5 ng/ml) and P. falciparum (chloroquineresistant W2 clone, IC 50 = 8.0 ng/ml), which compared well with artemisinin used as a control (IC 50 = 10 and 6.3 ng/ml, respectively) .…”
Section: Antimalarial Antiprotozoal Antituberculosis and Antiplatelmentioning
confidence: 99%